2023
DOI: 10.3390/ijms24108463
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Biodistribution of Fragmented Polypropylene Microplastics in ICR Mice

Abstract: Currently, polypropylene (PP) is used in various products, thus leading to high daily exposure in humans. Thus, it is necessary to evaluate the toxicological effects, biodistribution, and accumulation of PP microplastics in the human body. In this study, administration of two particle sizes of PP microplastics (approximately 5 and 10–50 µm) did not lead to any significant changes in several toxicological evaluation parameters, including body weight and pathological examination, compared with the control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In this study, the no-observed-adverse-effect level (NOAEL) was estimated to be less than 1,000 mg/kg in male mice and <500 mg/kg in female mice [ 39 ]. An evaluation of the toxicity of polypropylene fragments through oral administration in mice showed that the NOAEL for PP microplastics was greater than 2,000 mg/kg [ 40 ]. Nonetheless, it is worth noting that intratracheal instillation of PP microplastic in mice induces inflammation at a dose of 2.5 mg/kg, as demonstrated in a previous study [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the no-observed-adverse-effect level (NOAEL) was estimated to be less than 1,000 mg/kg in male mice and <500 mg/kg in female mice [ 39 ]. An evaluation of the toxicity of polypropylene fragments through oral administration in mice showed that the NOAEL for PP microplastics was greater than 2,000 mg/kg [ 40 ]. Nonetheless, it is worth noting that intratracheal instillation of PP microplastic in mice induces inflammation at a dose of 2.5 mg/kg, as demonstrated in a previous study [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research is ongoing to understand the potential impact of microplastics on the human immune system, and evidence has been found of chronic inflammation and homeostasis disturbances in animal studies and the activation of innate immunity in human lung cells [18,19]. Collectively, cellular and animal experiments have elucidated the role of microplastics in inducing oxidative stress, disrupting cellular structures, triggering inflammatory responses, lipid metabolism disturbances, gut microbiota dysbiosis, and neurotoxicity [20,21]. The studies included in this compilation offer valuable insights into the biodistribution and toxic effects of N/MPLs, and their findings underscore the critical influence of particle size, polymer composition, and exposure duration in determining the extent of damage caused by N/MPLs.…”
mentioning
confidence: 99%